2001
DOI: 10.1159/000055996
|View full text |Cite
|
Sign up to set email alerts
|

Dendritic Anomalies in a Freezing Model of Microgyria: A Parametric Study

Abstract: Despite easier recognition of focal developmental cortical anomalies with modern morphological and functional imaging techniques, mechanisms leading to refractory epilepsy are still poorly understood. Recent experimental studies have shown that not only the lesioned cortex, but also the apparently normal adjacent cortex undergoes morphological changes and alterations of its neuronal connections. To further investigate the modifications of the cortex surrounding a focal maldevelopmental lesion, we applied a fre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 21 publications
2
4
0
Order By: Relevance
“…Increased recurrent excitatory connections can underlie network hyperexcitability. Longer basal dendrites are present in layer 5 corticothalamic pyramidal cells in approximately 3 months old FL rats, while layer 3 corticocortical cells have a simplified dendritic branching pattern and fewer spines (Di Rocco et al 2001. Although these studies were done in much older rats, they are in agreement with the results presented here.…”
Section: Discussionsupporting
confidence: 91%
“…Increased recurrent excitatory connections can underlie network hyperexcitability. Longer basal dendrites are present in layer 5 corticothalamic pyramidal cells in approximately 3 months old FL rats, while layer 3 corticocortical cells have a simplified dendritic branching pattern and fewer spines (Di Rocco et al 2001. Although these studies were done in much older rats, they are in agreement with the results presented here.…”
Section: Discussionsupporting
confidence: 91%
“…The results provided in this study, compared with those of our previous studies on layer 3 corticocortical neurons [6,9], suggest that the dendritic architecture is differently affected in different neuronal populations located in the paramicrogyric cortex. In fact, in contrast to the simplification occurring in the basal dendrites of associative neurons, layer 5 corticothalamic neurons display longer dendritic branches.…”
Section: Discussionsupporting
confidence: 62%
“…In addition, it has been observed that the generator of epileptiform activity is outside the microgyrus in the adjacent cortex [11]. We have previously demonstrated that the dendritic branching pattern of layer 3 associative neurons located in the paramicrogyric cortex is simplified and that dendritic spines are substantially reduced, possibly as a consequence of epileptogenic activity [6,9]. Here we report the dendritic architecture of corticothalamic neurons located in layer 5 of the cortex surrounding the experimentally induced lesion.…”
Section: Introductionmentioning
confidence: 74%
See 1 more Smart Citation
“…We targeted physiologically confirmed regions of M1 with injections of NMDA and BDA (Jiang et al 1993; Johnson and Burkhalter 1997; Di Rocco et al 2001). This method of retrograde tracing is reliable and provides a well-defined preservation of ultra-structure, displaying organization of circuits (Jiang et al 1993; Johnson and Burkhalter 1997).…”
Section: Discussionmentioning
confidence: 99%